3D-printed microfluidic device for the analysis of intestinal tissue ex vivo - McLean, Ian, author; Schwerdtfeger, Luke, author; Wilson, Jessie, author; Henry, Charles, author; Tobet, Stuart, author (Colorado State University. Libraries, 2017)
Currently, most in vitro experimental models of the intestine rely upon cell lines, and consequently, lack the diverse representation of cells present in vivo. Slices of intestine, removed from living organisms, offer a better representation of in vivo physiology. However, current techniques for maintaining intestinal tissue in vitro are not capable of recapitulating the in vivo environment. This project utilizes 3D printing and microfluidic principles to design a device that delivers differential flows of media across the two surfaces of intestinal tissue. The device will enable the investigation of complex biological questions that previous models have been unable to address.
192 - Ian Cook McLean
Keywords: microfluidic; tissue culture; microbiome